Full Ka‐band right‐angle transition from substrate integrated waveguide to air‐filled rectangular waveguide. Issue 22 (13th October 2015) - Dong, Jun; Yang, Ziqiang; Peng, Hao; Yang, Tao
Abstract : A full Ka‐band right‐angle transition from a substrate integrated waveguide (SIW) to an air‐filled rectangular waveguide is proposed. A two‐step ridged waveguide and the SIW with an etched slot are jointly designed to obtain a better electric field and impedance matching between the SIW and the air‐filled rectangular waveguide. To verify the method, a back‐to‐back transition prototype at Ka‐band is designed, fabricated and measured. The measured results show that the insertion loss of a single transition is <0.55 dB over the entire Ka‐band from 26.5 to 40 GHz. Moreover, the 15 dB fractional bandwidth is increased from 25.7 to 40.9% compared with conventional right‐angle SIW‐to‐waveguide transition. This broadband transition can be a good candidate for broadband millimetre‐wave applications.